115k views
0 votes
Factor each expression. Show your complete solution.

27m^3-64

User Eyon
by
7.9k points

2 Answers

4 votes

Answer:

(3m−4)(9m2+12m+16)

Explanation:

this is difference of cubes (3m)^3 - (4)^3

now, apply difference of cubes formula

a^3−b^3 = (a−b)(a2+ab+b2)

where a=3m and b=4

(3m−4) ( (3)^2×(m)^2 + 4×3m + (4)^2)

(simplify)

(3m−4)(9m2+12m+16)

User Mari Murotani
by
7.8k points
4 votes

27m^3-64 = (3m)^3 - (4)^3

= (3m-4)((3m)^2 + (3m)(4) + (4)^2)

= (3m-4)(9m^2 + 12m + 16)

The factored form of 27m^3-64 is (3m-4)(9m^2 + 12m + 16)

User DarenW
by
7.3k points